Correlation of solar wind velocity with different parameters during geomagnetic disturbances - Dhakal, Sujan; Adhikari, Binod; Pudasainee, Kiran; Chapagain, Naryan Prasad; Pandit, Drabindra; Dahal, Subodh; Sapkota, Bhawani; Chhatkuli, Daya Nidhi (BIBECHANA, 2018)
We have studied the solar wind velocity and it’s relation with solar wind pressure, southward component of IMF-Bz, solar wind temperature (Tsw), solar wind density (Nsw) and geomagnetic indices during different geomagnetic disturbances. During disturbed days, there is a fluctuation of energy and plasma inside the magnetosphere, which changes the parameters like pressure, velocity, IMF-Bz, SYM-H and AE indices. The solar wind velocity shows very remarkable relationship with pressure. There is weak connection of solar wind pressure with IMF-Bz, although it is more geo-effective. BIBECHANA 16 (2019) 165-176